Protein restriction in chronic renal failure. Issue 3 (March 1993) - Kist-van Holthe tot Echten, J E; Nauta, J; Hop, W C; de Jong, M C; Reitsma-Bierens, W C; Ploos van Amstel, S L; van Acker, K J; Noordzij, C M; Wolff, E D
Abstract : The aim of the study was to investigate the effect of a protein restricted diet on renal function and growth of children with chronic renal failure. In a multicentre prospective study 56 children (aged 2-18 years) with chronic renal failure were randomly assigned to the protein restricted (0.8-1.1 g/kg/day) or the control group. All children were followed up by the same paediatrician and dietitian. After a follow up period of three years there was no significant difference in glomerular filtration rate between children on a protein restricted diet and children of the control group. There was no significant difference in weight with respect to height and height SD score between the protein restricted and the control group. Compliance with the protein restricted diet, as indicated by the prospective diet diaries and the serum urea:creatinine ratio, was good. This study shows that children with chronic renal failure do not benefit from a protein restricted diet.